Chaos control using a generalized extended time-delayed feedback method : application to a nonlinear pendulum - Queiroz, Arthur Rodrigues (2023)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2023.